2023
DOI: 10.3390/ijms24021473
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Gelatin-Agarose and Gelatin-Starch Blends Using Alkaline Solvent

Abstract: Plastic waste is a serious problem in modern society. Every day, mankind produces tons of waste that must be disposed of or recycled. The most common types of plastic waste are disposable tableware, bags, packaging, bottles, and containers, and not all are recycled. Therefore, there is a great interest in producing environmentally friendly disposable materials. In this study, modified gelatin blends using polysaccharides (e.g., agarose, starch) were produced to obtain a stable coating. Various techniques were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
1
0
0
Order By: Relevance
“…Agar's stable polysaccharide structure, decreased nutritional source, and limited water solubility at the investigated temperature of 58 °C makes it more resistant to degradation. The found data is in line with other studies [45] reporting slower degradation rates of agar.…”
Section: Biodegradationsupporting
confidence: 93%
“…Agar's stable polysaccharide structure, decreased nutritional source, and limited water solubility at the investigated temperature of 58 °C makes it more resistant to degradation. The found data is in line with other studies [45] reporting slower degradation rates of agar.…”
Section: Biodegradationsupporting
confidence: 93%
“…The results and their standard deviations are presented in Table 8. Based on the results obtained, it can be concluded that the introduction of polysaccharides into the blends leads to an increase in hardness and a decrease in elongation at break, and the results are comparable to the results of measurements performed for similar systems [42,[44][45][46][47]. The decrease in the value of the relative elongation of compositions containing polysaccharide may be related to the formation of a larger number of gelatine-polysaccharide bonds in the blend network, formed due to the presence of functional groups attached to the pyranose ring of agar and carrageenan.…”
Section: Mechanical Propertiessupporting
confidence: 79%
“…Determining the surface energy using three liquids, water, ethylene glycol, and diiodomethane, required measuring the contact angles of drops of each liquid on the surface of the samples. The measurement results in the form of average surface energy values are presented in Table 7 and correspond to the literature results [42,45]. The polar component for samples with added polysaccharides decreases with the increasing weight of these additives, which indicates a decrease in the hydrophilic properties of the blends made.…”
Section: Density Of the Blendssupporting
confidence: 78%
See 1 more Smart Citation
“…In accordance with the above, and to develop planet-friendly alternatives, numerous studies have been carried out on biocomposite and/or bioplastics, which seek to take advantage of biological material to replace conventional plastics [5][6][7][8][9][10][11][12][13][14][15][16][17][18], generating products with similar characteristics (high strength, durability, and robustness, among others), but with shorter degradation times and cleaner processes. However, the bioplastics industry faces challenges, such as high production costs, limited availability of raw materials, inferior mechanical properties compared to conventional plastics [19,20], the need for hightemperature composting facilities, and competition for land use.…”
Section: Introductionmentioning
confidence: 99%